Expression, Rapid Purification and Functional Analysis of DnaK from Rhodococcus ruber - Fan, Xin; Yuan, Yuan; Zhang, Fan; Ai, Lei; Wu, Zhonghao; Peng, Ren (Protein and Peptide Letters, 2021)
Background: Heat shock proteins (HSPs) represent a group of important proteins which are produced by all kinds of organisms especially under stressful conditions. DnaK, an Hsp70 homolog in prokaryotes, has indispensable roles when microbes was confronted with stress conditions. However, few data on DnaK from Rhodococcus sp. were available in the literature. In a previous study, we reported that toluene and phenol stress gave rise to a 29.87-fold and 3.93-fold increase for the expression of DnaK from R. ruber SD3, respectively. Thus, we deduced DnaK was in correlation with the organic solvent tolerance of R. ruber SD3. Objective: To elucidate the role of DnaK in the organic solvent tolerance of R. ruber SD3, expression, purification and functional analysis of Dnak from R. ruber SD3 were performed in the present paper. Methods: In this article, DnaK from R. ruber SD3 was heterologously expressed in E. coli BL21(DE3) and purified by affinity chromatography. Functional analysis of DnaK was performed using determination of kinetics, docking, assay of chaperone activity and microbial growth. Results: The recombinant DnaK was rapidly purified by affinity chromatography with the purification fold of 1.9 and the recovery rate of 57.9%. Km, Vmax and Kcat for Dnak from R. ruber SD3 were 80.8 μM, 58.1 nmol/min and 374.3 S-1, respectively. The recombinant protein formed trimer in vitro, with the calculated molecular weight of 214 kDa. According to in-silico analysis, DnaK interacted with other molecular chaperones and some important proteins in the metabolism. The specific activity of catalase in the presence of recombinant DnaK was 1.85 times or 2.00 times that in the presence of BSA or Tris-HCl buffer after exposure to 54 °C for 1h. E. coli transformant with pET28-dnak showed higher growth than E. coli transformant with pET28 at 43°C and in the presence of phenol, respectively. Conclusion: The biochemical properties and the interaction analysis of DnaK from R. ruber SD3 deepened our understanding of DnaK function. DnaK played an important role in microbial growth when R. ruber was subjected to various stress such as heating and organic solvent.
Keywords: expression and purification